Thermal performance evaluation of energy piles and energy foundations: A comprehensive review of thermal effectiveness testing methods - Ciapala, Bartlomiej; Georgiou, Giorgos S.; Aresti, Lazaros; Onoufriou, Toula; Florides, Georgios A.; Christodoulides, Paul (My University, 2025)
Energy Geo-Structures integrate ground-heat-exchanger pipe network in structural/foundation elements (energy piles, energy foundations), enabling buildings to exploit shallow geothermal energy. Adoption however, is restrained by thermal effectiveness uncertainty, across varied geological, climatic and operational conditions. A review study presented here consolidates evidence from laboratory, in-situ and operational studies to critically assess the evaluation techniques. Research publications on tests performed on energy piles/foundations are summarized by geographical distribution and the foundation and piping type, as well as exchanger configuration and test protocol. Constant-heat-flux Thermal Response Tests (TRTs) and constant-temperature Thermal Performance Tests (TPTs) dominate the literature. The TRT and TPT characteristics but also the operational tests and measurements are presented in detail. Among important findings are the following: large geographical disparities arise in recorded practice; TRT duration increases with pile diameter and groundwater flow affects predicted effective ground conductivity; TPT results demonstrate that inlet temperature, flow rate, and hydraulic connection architecture greatly affect heat-exchange rate; the limited long-term operational monitoring demonstrates that building load patterns, not soil properties, determine seasonal performance. Based on this review, the authors suggest a future challenge of a unified framework combining schematic piping diagrams, explicit unit definitions, and building-oriented operating-mode labels. Another future proposition could be multi-year experimental campaigns using TRTs, TPTs, and continuous monitoring on harmonized rigs in typical lithologies worldwide. Calibrated datasets could improve design guidelines, numerical models, and energy piles/foundations implementation as reliable, low-carbon, high-efficiency thermal energy systems.
Keywords: Thermal Response Test; Thermal performance test; Energy geostructures; Energy pile; Energy foundations